2022
DOI: 10.1177/15579883221074821
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Vitamin E and Omega-3 Fatty Acids on Reproductive Health Indices Among Male Workers Exposed to Electromagnetic Fields

Abstract: The present study aims to investigate the effects of using the supplementation of vitamin E and Omega 3 fatty acids on reproductive indices among workers in an automobile parts manufacturing plant. The effect of exposure to electromagnetic fields on certain sex hormones and sperm parameters will also be assessed. The participants were deployed into four groups as per the double-blind block randomization method. Semen parameters and sex hormones of the participants were analyzed before and after 3-month consump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…The participants were deployed into four groups as per the double-blind block randomization method. 6 The participants were divided into 4 groups in a double-blind random clinical trial study. Comparing the initial and final energy intake, macronutrients, and nutrients influential on target variables reveal no significant difference in any of the groups.…”
Section: Resultsmentioning
confidence: 99%
“…The participants were deployed into four groups as per the double-blind block randomization method. 6 The participants were divided into 4 groups in a double-blind random clinical trial study. Comparing the initial and final energy intake, macronutrients, and nutrients influential on target variables reveal no significant difference in any of the groups.…”
Section: Resultsmentioning
confidence: 99%
“…The significance of omega-3 fatty acids in relation to reproductive health is noteworthy due to their association with improved sperm parameters in certain research studies. These compounds have the capacity to enhance the quantity, motility, and morphology of sperm [62]. The seeds powder of Salvia hispanica are abundant in nutrients and encompass essential vitamins, minerals, and proteins.…”
Section: The Phenolic Compounds Of Salvia Hispanica Seeds Powder (Chia)mentioning
confidence: 99%
“…The same authors suggested that the link between diminished ω3FA doses and the augmented oxidative DNA destruction of spermatozoa was described in infertile men, endorsing that insufficient intake of ω3FAs could be involved in infertility ( Figure 2 ). Recently, [ 58 ] investigated the efficacy of vitamin E (100 mg) and ω3FA (300 mg/day) addition on reproductive catalogs among employees in an automobile portions industrial vegetable. As several authors indicated, ω3FA dietary intake can enhance the antioxidative defense, βeta-oxidation in sperm mitochondria, reduce oxidative stress, sustain sperm membrane, and enhance sperm health and function ( Figure 2 ), thus alleviating male infertility [ 20 , 56 , 57 , 58 ].…”
Section: Dietary Nutrientsmentioning
confidence: 99%
“…Recently, [ 58 ] investigated the efficacy of vitamin E (100 mg) and ω3FA (300 mg/day) addition on reproductive catalogs among employees in an automobile portions industrial vegetable. As several authors indicated, ω3FA dietary intake can enhance the antioxidative defense, βeta-oxidation in sperm mitochondria, reduce oxidative stress, sustain sperm membrane, and enhance sperm health and function ( Figure 2 ), thus alleviating male infertility [ 20 , 56 , 57 , 58 ].…”
Section: Dietary Nutrientsmentioning
confidence: 99%